Thermodynamic analysis of using chemical-looping combustion in Allam-Z cycle instead of common combustion. (15th February 2022) - Liu, Zhiyuan; Li, Zhiyong; Zhang, Yuan; Zhang, Yidian; Zhao, Ben
Highlights: A modified Allam-Z cycle using chemical-looping combustion instead of oxy-fuel combustion is proposed. The selection of oxygen carriers and detailed parametric sensitivity are investigated. The electric efficiency of the CLC-Allam cycle is about 9.5 percentage points higher than the original Allam-Z cycle. Abstract: This paper proposes a modified Allam-Z cycle that uses chemical-looping combustion (CLC) instead of traditional combustion, called CLC-Allam cycle. Under the same cycle and components conditions, the electric efficiency of the CLC-Allam cycle is about 9.5 percentage points higher than the original Allam-Z cycle. The investigation of selecting oxygen carriers in the CLC-Allam cycle reveals that cupric oxide always provides the highest fuel conversion in the supercritical carbon dioxide (SCO2 ) atmosphere and is thus believed to be the best oxygen carrier among the five investigated metallic oxides. The subsequent analysis focuses on parametric sensitivity and shows that (1) the inlet temperature and isentropic efficiency of CO2 pump have little effect on cycle efficiency, beneficial to enhance the system robustness; (2) the isentropic efficiency of turbine and compressor has a more significant influence on the cycle electric efficiency than the pump; (3) an optimal SCO2 turbine inlet temperature exists for the CLC-Allam cycle and the oxygen carrier will not encounter sintering or melting problems under the optimal temperature.